Pengaruh Penerapan E-Samsat dan Pajak Progresif Terhadap Penerimaan Pendapatan Pajak Kendaraan Bermotor - Vania Rakhmadhani; Lilis Saidah Napisah (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2019)
This study aims to determine the effect of the application of E-Samsat and Progressive Tax on Motor Vehicle Tax revenue. In addition to knowing the effect partially and simultaneously regarding the application of E-Samsat and Progressive Taxes on revenue from Motor Vehicle Tax revenue. E-Samsat and Progressive Tax are independent variables, while revenue from Motor Vehicle Tax revenue is the dependent variable. The research method used in this research is descriptive and verification methods. The population in this study is the acceptance of e-Samsat, progressive tax and Motor Vehicle Tax in 2015-2019. The sampling technique used in this study is non-probability sampling with a purposive sampling method, so the sample in this study is the realization report of E-Samsat revenue, Progressive Tax and Motor Vehicle Tax in 2015-2019. The results of this study indicate that partially e-Samsat does not significantly influence the Motor Vehicle Tax revenue while the progressive tax has a significant effect on Motor Vehicle Tax revenue. Simultaneously, E-Samsat and Progressive Tax affect the acceptance of Motorized Vehicle Tax.